The Effect of Quality of Diet on Carcass and Meat Characteristics of Lambs at Ambient Temperatures of 20 and 30 o C - E. Rianto; M. K. Hill; J. V. Nolan (Faculty of Animal Science, Universitas Gadjah Mada, 2001)
Artikel dalam bentuk PDF